Impacts of Micro- and Nanoplastics on Photosynthesis Activities of Photoautotrophs: A Mini-Review - Li, Yunxue; Liu, Xianhua; Shinde, Shrameeta; Wang, Jiao; Zhang, Pingping (Frontiers in Microbiology, 2021)
The accumulation of micro- and nanoplastics (MNPs) has attracted immense global attention due to their adverse effects on the environment. Photosynthesis, an interface between non-living matter and living organisms, is very important for both energy flow and material circulation on our planet. Increasing evidence indicates that MNPs can pose direct or indirect stress effects on photoautotrophs, however, our knowledge about them is still limited. The purposes of this mini-review are (1) to review the latest literature of the impacts of MNPs on photosynthesis activities and summarize diverse impacts of MNPs on photosynthesis activities of different photoautotrophs (green plants, microalgae, and cyanobacteria); (2) to discuss the potential action mechanisms in both aquatic and terrestrial environments; and (3) various factors contributing towards these impacts. Additionally, this review provides key future research directions for both researchers and policymakers to better understand and alleviate the environmental impacts of MNPs on our planet.